Ženska kot avtorica in lik v novejši slovenski književnosti - Sturm-Schnabl, Katja (Jezik in slovstvo, 1998)
Until the late 1840s, women authors had not actively participated in Slovenian literature. Even those earned reputation in the aerly 20th century with their contributions to the central literary review Ljubljanski zvon, have not been subject of serious scientific analysis, but rather of misleading appraisal (e.g. Anton Slodnjak and Lino Legiša in their Hisotry of Slovenian Literature, Slovenska matica, 1956-1971). How their thematically and stilistically rich literature is treated by contemporary literary studies within the framework of gender studies, is illustrated using the example of Matija Kmet, story writer and playwright.
Keywords: Kmet, Marija; Slovene literature; slovenska književnost; ženska književnost; ženske; woman; pisateljice; 19./20. st.; literarne študije